Abusive supervision and workplace deviance as moderated by spiritual intelligence: an empirical study of Selangor employees - Roshayati Abdul Hamid,; Noor Hasni Juhdi,; Md Daud Ismail,; Nor Atiqah Abdullah, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Abusive supervision is described as subordinates’ perception of the extent to which supervisors engage in a sustained display of hostile verbal and nonverbal behaviours, excluding physical contact. Ample empirical evidence suggested that subordinates respond quite negatively to supervisor’s mistreatment by engaging in behaviours that are harmful to the organization and its members. However, little is known about the subordinates’ spiritual intelligence responses to abusive supervision. Spiritual intelligence is defined as the ability to apply and embody spiritual resources and qualities to enhance daily functioning and wellbeing. In this light the purpose of this study is to examine the relationship between abusive supervision as perceived by subordinates with workplace deviance by investigating how abusive supervision is moderated by spiritual intelligence and influence target-directed deviant acts (interpersonal and organizational deviance). Primary data were gathered from 136 completed questionnaires returned by employees of several manufacturing organizations in Selangor. The results showed that individuals with low spiritual intelligence strongly moderated the relationship between abusive supervision and workplace deviance compared to individuals with high spiritual intelligence.